Global Perspectives on Observing Ocean Boundary Current Systems - Todd, Robert E.; Chavez, Francisco P.; Clayton, Sophie; Cravatte, Sophie; Goes, Marlos; Graco, Michelle; Lin, Xiaopei; Sprintall, Janet; Zilberman, Nathalie V.; Archer, Matthew; Arístegui, Javier; Balmaseda, Magdalena; et al. (Frontiers in Marine Science, 2019)
Ocean boundary current systems are key components of the climate system, are home to highly productive ecosystems, and have numerous societal impacts. Establishment of a global network of boundary current observing systems is a critical part of ongoing development of the Global Ocean Observing System. The characteristics of boundary current systems are reviewed, focusing on scientific and societal motivations for sustained observing. Techniques currently used to observe boundary current systems are reviewed, followed by a census of the current state of boundary current observing systems globally. Next steps in the development of boundary current observing systems are considered, leading to several specific recommendations.